THE EXISTENCE OF SOCIAL MEDIA USERS: WORKING OR PLAYING? (INFORMATION CAPITALISM ANALYSIS) - Haryatno, Yulius Rudi (Mount Hope Economic Global Journal, 2023)
Indonesian people spend an average of 3 H 18 M per day for using social media. The activitiescarried out are very diverse, such as keeping in touch with friends and family, finding sparetime, reading news stories, watching live streaming, finding products to purchase, postingabout self-activities, etc. In Fuchs' view, social media users are part of digital labour. They areexploited by social media corporations, such as Facebook, Google, and others. Exploitationoccurs by commodifying and selling data from social media activity to advertising companies.This is not realized by the users. The aims of research are the first, to explore awareness andperceptions of IKBP students about their activities in social media. Second, to deconstruct userawareness regarding their existence when surfing social media. This research uses descriptivequalitative methods. The data in this research is accumulated through observation and FGD.This research took a sample of students from the The Christian Institute of Technology andBusiness of Bukit Pengharapan Tawangmangu, Karanganyar, Central Java. The resultsof this research indicate that users perceive that surfing in social media is part of playing,recreational activities and only to fill spare time. Meanwhile, if examined from Fuchs' theoryof information capitalism, social media users are digital labour that be exploited by digitalcorporations. This research is important so that users can use social media constructively, suchas accumulating capital and developing creativity. Don't waste time.